An assessment of magnetic and geochemical indicators of weathering and pedogenesis at two contrasting sites on the Chinese Loess plateau - Bloemendal, Jan; Liu, Xiuming; Sun, Youbin; Li, Ningning (Palaeogeography, palaeoclimatology, palaeoecology, 2008)
We present the results of high stratigraphic resolution measurements of magnetic and geochemical parameters sensitive to weathering and pedogenesis at two ∼ 2500 ky loess–palaeosol sequences on the Chinese Loess Plateau. The two sites, Duanjiapo and Luochuan, are located on a strong modern climatic gradient and should have been subject to a significantly different degree of precipitation and temperature during the period of loess accumulation. Comparison of the magnetic and geochemical parameters indicates a complex and inconsistent relationship both within and between sites. In particular, a previously suggested coherency between the amplitude of variations in magnetic susceptibility and the Rb/Sr ratio is shown not to be the case over the entire length of the sequence. This finding indicates that quantitative climatic reconstructions for Chinese loess which are based on any single magnetic or geochemical parameter should be treated with caution. ‘Difference’ plots, obtained by calculating the difference between coeval magnetic or geochemical parameters between the two sites appear may offer a useful means of characterising latitudinal gradients in weathering and soil forming intensity, and indicate increases in the intensity of summer monsoon strength after about 1200 ka and 600 ka.